Linkage of ABO blood groups with ischemic stroke - Bulur, Oktay; Korucu, Osman (Annals of Medical Research, 2021)
Aim: Like cancer and myocardial infarction, the cerebrovascular accident causes death and morbidity in adults. Ischemic stroke is the most common type of stroke. Predisposing conditions to other cardiovascular diseases similarly play a facilitating role for stroke. The association of ABO blood types with several illnesses as described in previous studies. In this retrospective observational study, our purpose is to show the contribution of ABO blood types in ischemic stroke patients. Our study is important because it is a rare analysis elucidating the link between ABO blood groups with IS risk in the Turkish population. Materials and Methods: 1,540 cases diagnosed with ischemic stroke and 20,863 healthy subjects determined as the control group was included in this research. Ischemic stroke cases and the healthy subjects were between 45-90 years old. Both these groups were examined for blood group analysis. Results: When the patients and healthy subjects were examined in terms of blood group distributions, the blood group type distribution within each group had similar characteristics. In terms of Rh status and Blood type distribution, Ischemic stroke cases, and the healthy subjects were not statistically different from each other. Conclusion: We were not able to show any relation between ischemic stroke and ABO blood type in our study.